Environmental Impact of Iron ore Mining in Bellary District, Karnataka: Using Geo-Spatial Techniques - Nayak, L.T. (National Geographical Journal of India, 2022)
Accurate and reliable information on the distribution of various earth resources, urbanization, industrialization etc., form the backbone of Environmental Impact Assessment study. Environmental Impact assessment ( EIA) is a process, used to identify the environmental, social and economic impacts of proposed and completed project. Environmental Impact Assessment in the wake of iron ore mining of Bellary district has been studied using 1991 and 2001 LANDSAT TM images downloaded from earth explorer and IRS LISS III image of 2011 downloaded from Bhuvan. The EIA index reveals that mining operation and associate activities have negative effects on physical environment of Bellary district. During 1991, 336.43 in 2001, 220.79 and in 2011, 459.29 hectares of forest area have been utilized to dump mining residual. During the process of transporting ore from mining site to industry the extracted ore had spread over 9537.78 hectares of area within a span of 30 years i.e., 1991 -2011. In 1991 there were 69.69 hectares of area covered by over burden materials spread by running water and other forces and in 2001 it increased to 281.06 hectares and in 2011 it has slightly reduced to 228.24 hectares. The forest area is not only used for dumping the mining residual but also most of the mine ore is extracted from the forest area which led into reduction of forest area to a greater extend.